Faktor yang Berdampak kepada Harga Saham saat Pemulihan Ekonomi Nasional Covid-19 - Labbaik, Muhamad; Mujtaba, Muhammad Irsyad Elfin; Primasatya, Rieswandha Dio; Lorensa, Like (Politeknik Ganesha Medan, 2024)
This study examines the relationship between ROA, ROE, EPS, CR, and NPM variables on stock prices after the Covid-19 pandemic. The research applies a quantitative method using secondary data. The data comes from Indonesian companies listed on the IDX for the period 2021-2022. The tests conducted include descriptive analysis and regression analysis. The financial data was sourced from the Osiris database provider. The results of this study show that the ROA variable has a significant impact on stock prices. The ROE variable does not have a significant impact, nor do the NPM, CR, and EPS variables. These findings can be useful for investors in gaining insights into the equity market in Indonesia. The limitation of this study is that it only uses five variables and focuses solely on the company's fundamental aspects. Other variables, such as non-accounting factors like the psychological aspect of Indonesian investors, could also be considered.